(untitled) - Griffin, Emory A. (Boston, 2008)
The most widely-used textbook for the communication theory course, A First Look at Communication Theory analyzes the major communication theories at a level that is appropriate for both lower- and upper-level courses. The 32 theories represented in the text reflect a mix of foundational and recent scholarship and strike a balance of scientific and interpretive approaches.
Keywords: Communication,Truyền thông; Philosophy,Triết lý